Desenvolvimento e Validação de Método indicativo de estabilidade para determinação de bromoprida na presença de parabenos por CLAE-DAD e estudo de compatibilidade fármaco-excipiente - Francielli Gelatti Bortoly Carvalho (2022)
Bromopride (BROP) is a drug that belongs to the class of antiemetics and prokinetics, often used in Brazil to treat nausea and vomiting, but not available in several countries. Considering the few studies found in the scientific literature and the lack of validated analytical methods for the analysis of bromopride (BROP), the objective of this study was to develop and validate a stability-indicating method for the quantitative determination of BROP in the presence of MPB and PPB excipients in pharmaceutical formulations and to carry out a drug-excipient compatibility study. The active pharmaceutical ingredients (APIs) were identified and characterized by observation of organoleptic characteristics, melting range, thin Layer Chromatography (TLC), High Performance Liquid Chromatography (HPLC), Ultraviolet spectrophotometry (UV) and Infrared Spectroscopy (IR). The HPLC method was developed on a liquid chromatograph coupled to a diode array detector (DAD) using an isocratic mode under the following conditions: C18 chromatographic column (150 × 4.6 mm - 3 μm), mobile phase composed of acetonitrile: water (52:48, v/v), pH 3.5, flow rate of 0.6 mL/min, injection volume of 20 μL, room temperature and wavelength of 276 nm. The method was validated according to the following parameters: selectivity, linearity, precision, accuracy, robustness, and limits of detection (LD) and quantification (LQ), according to international and national guidelines. A forced degradation study was carried out and the samples were stressed in an acidic, basic, oxidative medium, exposed to light and heat. The study of drug-excipient compatibility was performed by Infrared Spectroscopy (IR), each spectrum was recorded in the range of 4000 to 400 cm-1 using potassium bromide pellets. The techniques used to identify and characterize the APIs allowed them to be qualified as characterized chemical substances (CCS). The method linearity varied from 4-28 μg/mL for BROP with linear correlation coefficient (r)> 0.999, intermediate precision with relative standard deviation (RSD) 0.48% and repeatability with RSD 0.47%. The accuracy had mean recovery 99.60% ± 1.27% and good selectivity. In the forced degradation test, the standard sample remained stable under acidic stress conditions, neutral, photolytic under fluorescent white light, under basic degradation conditions there was a degradation of 22.12%, in oxidative degradation, 1.82% and in photolytic degradation under sunlight, 7.92%. The limit of quantification (LQ) and the limit of detection (LD) values calculated were 0.3 μL/mL and 0.09 μL/mL, respectively. The experimental value for LQ was 0.25 μL/mL, indicating good sensitivity of the method. The drug-excipient compatibility study showed few changes in the bands, which indicates evidence of interactions between drug and excipients in the combinations 1:1 of BROP + MPB, 1:1 of BROP + PPB and 1:1:1 of BROP + MPB + PPB The interactions are mainly attributed to hydrogen bonds and must be confirmed by thermoanalytical techniques. The developed method can determine the drug in oral solutions in a short period of time and with low use of organic solvent, and it can probably be used in the routine of quantitative analysis of quality control in pharmaceutical industries.